PENGARUH ASPEK KECERDASAN KOMPREHENSIF DALAM BAHAN AJAR TERHADAP PENCAPAIAN KOMPETENSI SISWA PADA PEMBELAJARAN FISIKA DI KELAS X SMAN 3 PADANG - Dewi Anggraini; Amali Putra; Zulhendri Kamus (PILLAR OF PHYSICS EDUCATION, 2016)
Students competence in physics lesson are not good reachable. One of the factor cause not reaching the students competency is using learning materials that have not been functioning as supporting appropriate learning activities for students both on the aspect of spiritual attitudes, social attitudes, knowledge, and skills. The purpose of research are to determine the effect of comprehensive intelligence aspects in learning materials to the achievement of the student competency in physics lessons at grade X SMAN 3 Padang. Type of research is Quasi Experiment with Randomized Control Group Only Design. The population of this research were the students grade X MIA SMAN 3 Padang who were registered in the 2015/2016. Sampling technique was Purposive Sampling. The data were analyzed using Chi Square test at significance level 0,05 and  degrees of freedom dk 1. Results of research show that using comperehsive intelligence aspect in learning materials has given significant effect  toward achievement of competency students knowledge in physics lessons in grade X SMAN 3 Padang, and there is no significant effect of comprehensive intelligence aspect in learning materials toward student competency in physics lessons at grade X SMAN 3 Padang to the student of spiritual attitudes, social attitudes, and skills